Single-petal rosette trajectory for 2D functional lung imaging - Frantz, Hanna; Speidel, Tobias; Rasche, Volker (Frontiers in Physics, 2024)
Purpose: The purpose of this study was to investigate the use of a 2D rosette trajectory for breath-hold and free-breathing real-time imaging of the lungs. Methods: Eight healthy volunteers underwent breath-hold magnetic resonance imaging (MRI) using two different parametrizations of the proposed single-petal rosette (SPR) trajectory, as well as radial ultra-short echo time (UTE) acquisition combined with the tiny golden-angle acquisition scheme. The additional free-breathing acquisitions of all trajectories were performed. The proposed technique was compared with the conventional radial UTE technique regarding image sharpness, signal-to-noise ratio (SNR), regional fractional ventilation (FV) for breath-hold and retrospective image-based self-gating, and real-time imaging capabilities. Results: Image sharpness significantly increased for gated SPR images compared to radial UTE for the end-expiratory stage; no significant difference was found for the self-gated end-inspiratory stage and the breath-hold acquisitions. The SPR trajectory performs significantly better than radial UTE concerning the SNR for breath-hold imaging, whereas no significant difference was found for self-gated images. Fractional ventilation values were comparable between SPR and radial UTE. The SPR real-time data showed a marked reduction in the aliasing artifacts with no apparent streaks. Conclusion: The second half of the petal of the SPR trajectory accomplishes rephasing while acquiring non-redundant k-space data, thus leading to a more efficient sampling of the k-space than that with the radial UTE sampling scheme, with a minimal increase in TR. This leads to the need of less read-outs to achieve the same SNR values and, thus, a reduction in scan time. For real-time application, the SPR approach resulted in a marked reduction of aliasing artifacts when compared to UTE.